Atividades anti-inflamatória e imunomoduladora de 2-(3-hidroxi-1-metil-2-oxoindolin-3-il) acrilonitrila (cisacn) na síndrome da asma e rinite alérgica combinadas (caras) experimental - Ferreira, Larissa Adilis Maria Paiva (2024)
Combined asthma and allergic rhinitis syndrome (CARAS) are a type 2 (TH2) airway immune response accompanied by an intense inflammatory process that widely affects the world population. Due to the compromise in the quality of life and the lack of specific pharmacotherapy, the search for new molecules becomes relevant. This study aimed to evaluate the treatment with the Morita Baylis-Hillman adduct CISACN in the CARAS experimental model. Therefore, female BALB/c mice were sensitized and challenged with ovalbumin (OVA) for a period of 43 days and treated with CISACN at doses of 6.25, 12.5 or 25 mg/kg. Treatment with the adduct decreased the infiltrate of eosinophils and neutrophil, hyperplasia and hypertrophy of goblet cells and tissue remodeling of the nasal cavity at 12.5 and 25 mg/kg, without statistical differences between the groups. Therefore, the dose of 12.5 mg/kg was chosen to continue the analysis. In addition, CISACN reduced eosinophil and neutrophil infiltration, reverting to baseline the number of eosinophils in the lung, lung tissue inflammation, goblet cell hyperplasia/hypertrophy, airway hyperactivity, reducing smooth muscle hyperplasia/hypertrophy, and the thickness of the extracellular matrix. CISACN reduced clinical signs of allergic rhinitis, such as nasal rubbing and sneezing, in a histamine-induced nasal hyperreactivity trial. The immunomodulatory effect of CISACN was observed via the reduction of serum levels of total IgE, OVAspecific IgE and the number of eosinophils in the blood. The treatment also decreased the production of IL-33, TSLP, IL-17, TNF-α and TGF-β with an immunoregulatory effect via a decrease in IL-5, IL-4, IL-13, TH2 cytokine profile, dependent on the increase of IFN-γ, a TH1 cytokine profile, but independent of IL-10, a T regulator (Treg) cytokine profile. In the molecular analyzes we observed that CISACN decreased, in pulmonary granulocytes, the activation of the p-p38MAPK and p-NF-κB signaling pathway, independent of p-ERK1/2 MAPK. Therefore, the results obtained in this work demonstrate the anti-inflammatory and immunomodulatory effects of CISACN by reducing the migration of inflammatory cells to the airway tissues of animals with CARAS, the cytokines responsible for the development and maintenance of the CARAS profile and a decrease in the cellular signaling pathway responsible to produce these signaling molecules. The scientific support provided by this study makes it possible to use CISACN in pharmaceutical formulations to be tested in the treatment of inflammatory airway diseases.